NETs drive myocardial fibrosis in hypertension via an NF-κB/ferroptosis axis - Tu, Qingxian; Gong, Xiaowei; Yuan, Xiaoxi; Tang, Yiyue; Huang, Runze; Jiang, Qianfeng; Li, Wei (Frontiers in Immunology, 2026)
IntroductionHypertensive heart disease (HHD) is characterized by chronic pressure overload leading to myocardial remodeling and fibrosis. While inflammation and cell death pathways contribute to fibrogenesis, the mechanistic role of neutrophil extracellular traps (NETs) remains insufficiently understood. This study investigated whether NETs exacerbate myocardial fibrosis in spontaneously hypertensive rats (SHRs) through activation of the nuclear factor-κB (NF-κB) signaling pathway and ferroptosis.MethodsMale SHRs and normotensive Wistar-Kyoto (WKY) rats were used to assess blood pressure, cardiac function, and myocardial fibrosis via echocardiography, histology, and Western blotting. Transcriptomic profiling, immunofluorescence, and ELISA quantified NET-associated and ferroptosis-related markers. H9c2 cardiomyoblasts were treated with angiotensin II (Ang II) or isolated NETs, with or without DNase I, Ferrostatin-1 (Fer-1, ferroptosis inhibitor), or JSH-23 (NF-κB inhibitor). Gene and protein expression were analyzed by qPCR and Western blotting to elucidate NET-induced molecular mechanisms.ResultsSHRs exhibited elevated systolic blood pressure, reduced ejection fraction, and marked myocardial fibrosis with increased collagen deposition. Transcriptomic and proteomic analyses revealed significant upregulation of NETs and ferroptosis-related genes, accompanied by NF-κB pathway enrichment. Myocardial and serum levels of citrullinated histone H3 and myeloperoxidase were elevated, confirming enhanced NET formation. In H9c2 cells, NETs induced ferroptotic features—elevated ACSL4, reduced FTH1 and GPX4—and activated NF-κB signaling, leading to increased expression of α-SMA, fibronectin, collagen II, and MMP3. DNase I pretreatment or inhibition of ferroptosis or NF-κB each mitigated these changes, with combined inhibition exerting the strongest suppressive effect.DiscussionThese findings identify a pathogenic NETs/NF-κB/ferroptosis axis that drives hypertensive myocardial fibrosis. NETs promote oxidative stress and iron-dependent cell death in cardiomyocytes, amplifying inflammatory and profibrotic signaling. Therapeutic targeting of NETs formation or downstream ferroptotic and NF-κB pathways may thus attenuate fibrotic remodeling and preserve cardiac function in HHD. This study provides mechanistic insight into how sterile inflammation orchestrates myocardial injury and highlights novel intervention strategies against hypertensive cardiac fibrosis.